GAMBARAN GAYA HIDUP PENDERITA HIPERTENSI DI RW 3 KELURAHAN SUMAMPIR KECAMATAN PURWOKERTO UTARA, KABUPATEN BANYUMAS - Ikit Netra Wirakhmi; Dwi Novitasari (Dinamika Journal : Pengabdian Masyarakat, 2019)
Hypertension is still a big challenge in Indonesia and is a health problem with a high prevalence. Based on data from Puskesmas 2 Purwokerto Utara, hypertension sufferers in RW 3 Sumampir Village, Purwokerto Utara District, Banyumas Regency are quite a lot. Management of hypertension can be done using drugs or by way of lifestyle modification. The expected goals of community service are the availability of independent groups of people with hypertension, the availability of digital tensimeters, digital scales and can operate well, describing physical activity, eating patterns, resting habits and smoking habits of hypertensive patients. The service method is done through health education (lectures and discussions). Based on the results of community service in RW 3 Sumampir Village, Purwokerto Utara District, Banyumas Regency it can be concluded that community service activities can increase the skills of hypertension sufferers on the operation of digital tensimeter devices and digital scales, get an overview of physical activity, eating patterns, resting habits and smoking habits of hypertensive sufferersKeywords: Hypertension, Lifestyle